Enhanced Drug Delivery with Oil-in-Water Nanoemulsions: Stability and Sustained Release of Doxorubicin - Hwang, Juyoung; Park, Ji Yeong; Kang, Jio; Oh, Nuri; Li, Chen; Yoo, Chung Yul; Um, Wooram; Kwak, Minseok (Macromolecular Rapid Communications, 2024)
In this study, oil-in-water nanoemulsions are prepared, an isotropic mixture of oil, surfactant, and cosurfactants. The nanoemulsions exhibit stable structures and are capable of efficiently encapsulating hydrophobic drugs such as doxorubicin (Dox). Compared to polymeric micelles, nanoemulsions demonstrate enhanced stability and loading capacity for Dox. Furthermore, nanoemulsions release Dox steadily over 14 days, with 51.6% released within the initial 24 h and up to 80% over the subsequent period. These properties suggest that nanoemulsions can mitigate the side effects related to the burst release of Dox, thereby improving therapeutic efficacy and safety. Additionally, nanoemulsion-treated cardiomyocytes show increased viability compared to those treated with free Dox, indicating the potential of nanoemulsions to alleviate Dox-induced cardiotoxicity. Overall, nanoemulsions hold promise as versatile and efficient drug carriers for improving cancer treatment outcomes.
Keywords: 4T1 cells; Cardiotoxicity; Doxorubicin; Drug-delivery systems; H9c2 cells; Isotropic mixtures; Mixture of oil; Nanoemulsion; Oil-in-water; Sustained release; Animals; Antibiotics, Antineoplastic; Cell Survival; Delayed-Action Preparations; Doxorubicin; Drug Carriers; Drug Delivery Systems; Drug Liberation; Emulsions; Humans; Nanoparticles; Oils; Particle Size; Water; 4T1 cell; cardiotoxicity; chemotherapy; drug delivery system; H9C2 cell